Review on feverfew, a valuable medicinal plant - Pourianezhad Farzaneh; Tahmasebi Sara; Abdusi Vahid; Nikfar Somayeh; Mirhoseini Mahmoud (Shahrekord University of Medical Sciences, 2016)
Background and Aims: Feverfew (Tanacetum parthenium) is a valuable medicinal plant from Asteraceae family with various pharmacological and therapeutic properties. In this article we reviewed the various aspects of feverfew including botanical characteristics, cultivation and production and medicinal and clinical uses.Material and Methods: Google Scholar, PubMed, EBSCO, Directory of open access journals (DOAJ), EMBASE, and Web of Science were searched using the keywords feverfew and parthenolide. Results: The essential oil of feverfew is frequently used in pharmaceutical and cosmetic industries. Parthenolide is the most important active component of feverfew that is used for the treatment of a wide variety of diseases such as fever, migraine headache, and rheumatoid arthritis.Conclusion: Feverfew has several positive clinical uses and has the potential to be considered as a new drug for the treatment of some diseases.